2022
DOI: 10.1101/2022.09.01.506188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Phylogeny of the Brassicaceae Provides Important Insights into Gene Discordance

Abstract: The mustard family (Brassicaceae) is a scientifically and economically important family, containing the model plant Arabidopsis thaliana and numerous crop species that feed billions worldwide. Despite its relevance, most published family phylogenies are incompletely sampled, generally contain massive polytomies, and/or show incongruent topologies between datasets. Here, we present the most complete Brassicaceae genus-level family phylogenies to date (Brassicaceae Tree of Life, or BrassiToL) based on nuclear (&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(72 citation statements)
references
References 126 publications
11
61
0
Order By: Relevance
“…The selection of genes may nonetheless influence the topology. We found that while the Brassicaceae species tree based on the complete Brassicaceae set as used in the original publication supports Arabideae as sister to clades A, B and C (Nikolov et al 2019), the tree based on the syntenic subset we analyzed here followed the same topology we detected for other gene sets without paralogs, with clades A and C as sister to Arabideae and clade B. Interestingly, a recent genus-level phylogeny of Brassicaceae also found different topologies at deep nodes depending on filtering level, with the species tree inferred from the combined Angiosperm353 and Brassicaceae gene sets supporting topology B and stricter filtering resulting in a species tree more similar to our topology A (Hendriks et al 2022). Altogether, we conclude that the use of synteny for selecting genes for phylogenomics does not necessarily perform better than more established methods when it comes to the topology of the resulting species tree with regards to tree resolution.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The selection of genes may nonetheless influence the topology. We found that while the Brassicaceae species tree based on the complete Brassicaceae set as used in the original publication supports Arabideae as sister to clades A, B and C (Nikolov et al 2019), the tree based on the syntenic subset we analyzed here followed the same topology we detected for other gene sets without paralogs, with clades A and C as sister to Arabideae and clade B. Interestingly, a recent genus-level phylogeny of Brassicaceae also found different topologies at deep nodes depending on filtering level, with the species tree inferred from the combined Angiosperm353 and Brassicaceae gene sets supporting topology B and stricter filtering resulting in a species tree more similar to our topology A (Hendriks et al 2022). Altogether, we conclude that the use of synteny for selecting genes for phylogenomics does not necessarily perform better than more established methods when it comes to the topology of the resulting species tree with regards to tree resolution.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, we ran ASTRAL for all gene sets against the Brassicaceae phylogeny following the prevailing species tree hypothesis (also shown in Fig. 1) derived from three recent comprehensive phylogenomics studies (Huang et al 2016; Nikolov et al 2019; Hendriks et al 2022) and compared the normalized quartet scores. The scores roughly followed the same trend as mean bootstrap support, with datasets comprised mainly of orthologs having higher values than those comprised of or including paralogs (with the exception of the two smallest gene sets, for which no reliable estimate could be obtained).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the emergence of standardized practices for generating and analysing RNAseq data (Conesa et al ., 2016) offers support towards meaningful conclusions on transcriptional plasticity under environmental changes. Here, we address transcriptional responses of Biscutella laevigata , a widespread species belonging to an early diverging Brassicaceae genus (Couvreur et al ., 2010; Hendriks et al ., 2022) to different environments. Being a textbook example of autopolyploidy linked to ice ages (Manton, 1937; Parisod & Besnard, 2007), diploids of B. laevigata occur across major ecological gradients (e.g.…”
Section: Introductionmentioning
confidence: 99%